Validation of a newly developed multi-dimensional instrument to assess maternal perceptions of the quality of institutional postnatal care services in Sri Lanka - Sashimali Wickramasinghe; Wasantha Gunathunga; Nilmini Hemachandra (Journal of the College of Community Physicians, 2019)
Introduction: Postnatal period is an important period during which both mother and the newborn adjust to the new environment. High quality services should be provided during this period in order to prevent adverse health outcomes. Patients' perception of the care received by them is considered an important attribute in the assessment and improvement of quality of health care. However, this should be assessed using a valid and reliable instrument.   Objectives: To assess the psychometric properties of a newly developed instrument to assess the mothers’ perception of the quality of institutional postnatal care in Sri Lanka   Methods: The instrument was validated among 200 mothers who had undergone normal vaginal delivery in Colombo North Teaching Hospital and were in the immediate postnatal period. The factor structure of the instrument, its internal consistency and test retest reliability were assessed as main outcomes.   Results: Following exploratory factor analysis, the instrument consisted of 23 items. Three main domains identified were interpersonal care, technical care and information, and ward facilities and cleanliness. The three factor model identified was able to explain 58.9% of the total variance of the scale. The Cronbach’s alpha value for the total scale was 0.94. The Spearman’s rank correlation coefficient value for the test retest reliability was 0.94.   Conclusions: The instrument developed for assessment of maternal perception of the quality of postnatal care reported satisfactory level of validity and reliability, thus recommended to be used for improving care provision.